Walt Disney´s Nine old men : - Docter, Pete (Disney editions, 2012)
This box set of nine flip books pays tribute to Walt Disney's original animators-the Nine Old Men. Each flip book features an iconic scene from an animated Disney feature in its original line-drawn form, having been selected from among a wide range of films for great movement and classic characters. The films include Alice In Wonderland, Dumbo, Fantasia, Peter Pan, Bambi, Lady and the Tramp, 101 Dalmatians, and Pinocchio.